Increased basal ganglia binding of 18F‐AV‐1451 in patients with progressive supranuclear palsy. Issue 1 (6th October 2016) - Smith, Ruben; Schain, Martin; Nilsson, Christer; Strandberg, Olof; Olsson, Tomas; Hägerström, Douglas; Jögi, Jonas; Borroni, Edilio; Schöll, Michael; Honer, Michael; Hansson, Oskar
ABSTRACT: Background: Progressive supranuclear palsy (PSP) is difficult to diagnose accurately. The recently developed tau PET tracers may improve the diagnostic work‐up of PSP. Methods: Regional tau accumulation was studied using 18 F‐AV‐1451 PET in 11 patients with PSP and 11 age‐matched healthy controls in the Swedish BioFinder study. Results: 18 F‐AV‐1451 standard uptake volume ratios were significantly higher in the basal ganglia in PSP patients when compared with controls (globus pallidus 1.75 vs 1.50; putamen 1.51 vs 1.35). Retention in the basal ganglia was correlated with age in both groups ( r = .43–.78, P < .05). In PSP, we observed a significant correlation between clinical deterioration measured with the PSP rating scale and standard uptake volume ratios in the globus pallidus ( r = .74, P < .05). However, no 18 F‐AV‐1451 retention was observed in the cerebral cortex or white matter of either PSP patients or controls, and autoradiography did not reveal any specific binding of AV‐1451 to PSP tau aggregates. Conclusion: We found higher 18 F‐AV‐1451 retention in the basal ganglia of PSP patients when compared with healthy elderly controls, but also increases with age in both controls and patients. As a result of the overlap in retention between diagnostic groups and the age‐dependent increase present also in controls, 18 F‐AV‐1451 PET might not reliably distinguish individual patients with PSP from controls. However, further studies are needed to evaluate whether 18 F‐AV‐1451 PET might be useful as a progression marker in clinical PSP trials. © The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.